Libraries and Extension: Partnering to Expand Access Through Ebooks - Kristen Mastel; Scott Chazdon; Mary Hockenberry Meyer; Matthew Russell; Diane Narem (Issues in Science and Technology Librarianship)
Providing timely information—when and where people need it—has long been a goal of University of Minnesota Extension. This objective coincides with University of Minnesota Libraries' support of open access publishing and the use of Creative Commons to remove content from paywalls. Many libraries at land-grant institutions have developed their own publishing programs to support open scholarship, leveraging the depth of their expertise in research dissemination. This article highlights three examples of Extension ebooks published in partnership with the University of Minnesota Libraries.